Adsorption Behavior of Fluorocarbon Surfactants on Polytetrafluoroethylene Surface - Fei Yan; Cheng Ma; Qingtao Gong; Wangjing Ma; Zhiqiang Jin; Zhicheng Xu; Lei Zhang; Lu Zhang (Colloids and Interfaces)
By using the sessile drop method, the wetting properties of nonionic fluorocarbon surfactants (FNS-1 and FNS-2) and anionic fluorocarbon surfactant (FAS) solutions on the surface of polytetrafluoroethylene (PTFE) were investigated. Meanwhile, the effects of surfactant concentration on the contact angle, adhesion tension, PTFE–liquid interfacial tension, and work of adhesion of the fluorocarbon surfactant with different structures were detected. The results demonstrate that the adsorption amount of the three fluorocarbon surfactants at the air–liquid interface is 1.5~2 times higher than their adsorption amount at the PTFE–solution interface. Before critical micelle concentration (CMC), the fluorocarbon surfactant molecules rely on their hydrophobic groups to adsorb on the PTFE surface. The smallest molecular size of FNS-2 results in the largest adsorption amount, while electrostatic repulsion and large steric hindrance result in the smallest adsorption amount for FAS. Above CMC, the fluorocarbon surfactants form semi-micelles to adsorb on the PTFE surface. The hydrophilic modification ability of the three fluorocarbon surfactants for the PTFE surface is stronger than that of reported surfactants, and the contact angle can be reduced to about 20° at high concentrations. The order of the hydrophilic modification ability is FNS-2 > FNS-1 > FAS. Hydrophilic EO groups can effectively enhance the hydrophilicity of FNS-1 and FNS-2. Due to the hydrophobic -CH3 group and the smaller adsorption amount, FNS-1 possesses a weaker hydrophilic modification ability than FNS-2. Investigating the adsorption behavior of fluorocarbon surfactants on the PTFE surface can help us to better utilize fluorocarbon surfactants. This could have broad implications for colloid and interface science.